Developmental functioning and medical Co‐morbidity profile of children with complex and essential autism. Issue 8 (5th May 2017) - Flor, Jaimie; Bellando, Jayne; Lopez, Maya; Shui, Amy
Abstract : Children with Autism Spectrum Disorders (ASD) may be characterized as "complex" (those with microcephaly and/or dysmorphology) or "essential" (those with neither of these two). Previous studies found subjects in the complex group exhibited lower IQ scores, poorer response to behavioral intervention, more seizures and more abnormal EEGs and brain MRIs compared to the essential group. The objective of this study was to determine if there are differences in complex versus essential subjects based on several developmental/psychological measures as well as certain medical comorbidities. This study utilized data from 1, 347 individuals (2–17 years old) well‐characterized subjects enrolled in Autism Treatment Network (ATN) Registry. Head circumference measurement and the Autism Dysmorphology Measure (ADM) were used by trained physicians to classify subjects as complex or essential. Significantly lower scores were seen for complex subjects in cognitive level, adaptive behavior and quality of life. Complex subjects showed significantly increased physician‐documented GI symptoms and were on a higher number of medications. No significant differences in autism severity scores, behavioral ratings and parent‐reported sleep problems were found. After adjusting for multiple comparisons made, adaptive scores remained significantly lower for the complex group, and the complex group used a significantly higher number of medications and had increased GI symptoms. Complex and essential autism subtypes may have distinct developmental and medical correlates and thus underlines the importance of looking for microcephaly and dysmorphology, when evaluating a child with autism. Determining this distinction in autism may have implications in prognosis, identifying medical co‐morbidities, directing diagnostic evaluations and treatment interventions. Autism Res 2017, 10: 1344–1352 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.